THE LEGAL EFFECTIVENESS OF LAND REDISTRIBUTION IMPLEMENTATION EX-CULTIVATION RIGHTS TITLE IN SEMPU, BABADAN AND SUGIHWARAS VILLAGES KEDIRI, EAST JAVA - Nurbaedah, Nurbaedah (Jurnal Pembaharuan Hukum, 2023)
This research aims to analyze the effectiveness of the implementation of land redistribution ex-Cultivation Rights Title as well as analyze its obstacles and solutions in Sempu, Babadan, and Sugihwaras Villages, Kediri, East Java. This study used empirical research methods with primary data as the main data. This research data uses primary data, namely interviews and secondary data which include laws, regulations on agrarian affairs, books and journals that study agrarian reform. The results of this study explain that the priority of implementing agrarian reform for ex-Cultivation Rights Title land that has expired its Cultivation Rights Title and within 1 year has not applied for a permit extension. The implementation of land redistribution in Sempu, Babadan and Sugihwaras Village, Kediri, East Java approximately 1,766 fields of former Cultivation Rights Title of PT Sumber Sari Petung has been 100% completed. The utilization of this former Cultivation Rights Title land is still used as agricultural land. The implementation of land redistribution of ex-Cultivation Rights Title to Use Enterprises in these three villages legal effectiveness has been achieved because redistribution can resolve agrarian conflicts. The obstacles encountered in land redistribution are limited human resources and limited time to complete land redistribution. The significance of this research lies in the importance of public and private sector participation in supporting the implementation of land redistribution, so that it can optimally realize agrarian reform.